Uji Beberapa Konsentrasi Ekstrak Bawang Merah dan Lama Perendaman terhadap Perkecambahan Tanaman Seledri (Apium graveolens L.) - Susianti, Helda; Palupi, Dora; Yus Dwi Yanti; Limartaida Siahaan; Mahmudin (Fakultas Pertanian Universitas Ratu Samban, 2025)
Celedry (Apium graveolens L.) is one type of vegetable that has many benefits, both used for daily needs and used as medicine or vitamins to determine the optimal concentration of red onion extract and soaking duration for the germination of celery plants. This study was conducted at the Agricultural Laboratory of the State Manufacturing Polytechnic of Bangka Belitung from January to February 2025. The experimental design used was a Completely Randomized Design (RAL) with 2 factors. The first factor is concentration, with four levels namely the concentration of red onion extract 0%, 10% (K2), 20% (K3), 30% (K4). The second factor is the duration of soaking for 24 hours (W1) and 48 hours (W2). The observed variables are total wet weight of sprouts (g), total dry weight of sprouts (g), length of sprout shoot (cm), and length of sprout root (cm). The data from the research were analyzed using ANOVA variance and further tested using the DMRT test at a 5%. The research results indicate that the treatment with different concentrations of red onion extract and the duration of soaking significantly affects the total wet weight of the sprouts, the total dry weight of the sprouts, and the length of the sprout apex, but does not significantly affect the length of the root apex of celery plants. The interaction between 10% onion extract concentration and 24 hour soaking effectively increases total root weight, dry weight, and seedling shoot length of celery.